Explanatory Pluralism and the (Dis)Unity of Science: The Argument from Incompatible Counterfactual Consequences - Gijsbers, Victor (Frontiers in Psychiatry, 2016)
What is the relationship between different sciences or research approaches that deal with the same phenomena, for instance, with the phenomena of the human mind? Answers to this question range from a monist perspective according to which one of these approaches is privileged over the others, through an integrationist perspective according to which they must strive to form a unity greater than the sum of its parts, to an isolationist perspective according to which each of them has its own autonomous sphere of validity. In order to assess these perspectives in this article, I discuss the debates about the unity of science and about explanatory pluralism. The most pressing issue turns out to be the choice between the integrative and the isolationist perspective: the question is whether the integrative tendencies in science should be fully indulged in, or whether they should be held in check by acknowledging that a certain amount of isolation is necessary. I argue that the issue can be further distilled into the question of whether two true explanations of the same fact can ever fail to be combinable into one single explanation. I show that this can indeed be the case, namely when the explanations have incompatible counterfactual consequences, something that is often the case when we try to combine explanations from different sciences or research approaches. These approaches thus embody perspectives on the world that are to a certain extent autonomous. This leads to the conclusion that although interdisciplinarity may have many advantages, we should not take the project of integration too far. At the end of the day, the different research approaches with their different perspectives and insights must remain precisely that: different and somewhat disunified.